Benefits of postural sway to succeed in goal-directed visual tasks - Bonnet, Cédrick T.; Kechabia, Yann-Romain; Magnani, Ivan; Polastri, Paula F. [UNESP]; Rodrigues, Sérgio T. [UNESP] (Elsevier, 2024)
When individuals stand, they sway and so have to maintain their balance. It is generally expected that task performance is worse when standing and swaying than when sitting and therefore not swaying. In contrast, we hypothesized that greater sway is associated with better task performance in the absence of external perturbations of posture. Twenty-four healthy, young adults performed two goal-directed, modified Stroop tasks (incongruent and reversed incongruent) in four body position conditions (standing against a vertical surface, and standing freely with a wide, standard or narrow stance). Centre of pressure (COP) sway, head sway, eye movements, visual attention, and task performance were recorded. Partial correlation analyses showed significant positive associations between task performance and some COP and head sway variables, after controlling for the level of visual attention. Analyses of variance with three factors (body position, task difficulty, target distance) also showed significant interaction effects between body position (and therefore postural sway) and the number of accurate target findings. The presence of these interactions showed that narrow stance was both the best body position for performing the incongruent task and the worst body position for performing the reversed incongruent task. Overall, COP sway and head sway can increase task performance. Hence, healthy, young adults in quiet stance appear to use sway to explore their environment more effectively. However, it should be borne in mind that our hypothesis was formulated solely with regard to healthy, young adults standing in quiet stance.
Keywords: Body position; Body sway; Modified Stroop task; Task performance; Young adults